2017
DOI: 10.1007/s40291-017-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Applications of Droplet Digital PCR in Oncology

Abstract: The clinical management of cancer has evolved in recent years towards more personalized strategies that require a comprehensive knowledge of the complex molecular features involved in tumor growth and evolution, and the development of drug resistance mechanisms leading to disease progression. Droplet digital PCR (ddPCR) has become one of the most accurate and reliable tools for the examination of genetic alterations in a wide variety of cancers because of its high sensitivity and specificity. ddPCR is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 153 publications
1
132
1
Order By: Relevance
“…Use of the sensitive ddPCR method to quantify the abundance of cells with the GNAQ p.Arg183Gln mutation allowed for an accurate quantification of the target nucleic acid samples. The reliability of ddPCR in the detection and quantification of DNA from FFPE samples has been already reported in other fields . The accuracy of this technique was further supported by its nondetection of the somatic mutation in the 14 samples not affected by capillary malformation, with an allele frequency of ≤0.5%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Use of the sensitive ddPCR method to quantify the abundance of cells with the GNAQ p.Arg183Gln mutation allowed for an accurate quantification of the target nucleic acid samples. The reliability of ddPCR in the detection and quantification of DNA from FFPE samples has been already reported in other fields . The accuracy of this technique was further supported by its nondetection of the somatic mutation in the 14 samples not affected by capillary malformation, with an allele frequency of ≤0.5%.…”
Section: Discussionsupporting
confidence: 93%
“…The reliability of ddPCR in the detection and quantification of DNA from FFPE samples has been already reported in other fields. [9][10][11] The accuracy of this technique was further supported by its nondetection of the somatic mutation in the 14 samples not affected by capillary malformation, with an allele frequency of ≤0.5%.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, Sanger sequencing, 10,19,21 PCR-based restriction fragment length polymorphism, 9 whole-exome sequencing 12 and next-generation sequencing have been used to detect KRAS mutations; however, droplet digital PCR is one of the most sensitive methods for the detection of mutations. 14,23 In this study, multiple types of KRAS mutations were observed in 83% (10/12) of NMLE foci and 78% (7/9) of MLE foci, with low allele frequencies. These observations suggest the presence of significant genetic heterogeneity in the early tumorigenesis of MCNs.…”
Section: Discussionmentioning
confidence: 49%
“…This higher rate of positive cases is probably the result of the mutation detection methods used. In previous studies, Sanger sequencing, PCR‐based restriction fragment length polymorphism, whole‐exome sequencing and next‐generation sequencing have been used to detect KRAS mutations; however, droplet digital PCR is one of the most sensitive methods for the detection of mutations …”
Section: Discussionmentioning
confidence: 99%
“…In this context, droplet digital PCR (ddPCR) provides the opportunity to fill the void in inversion characterization by detecting linkage between amplicons located at both sides of the breakpoint repeats, making it possible to jump long genomic distances. The ddPCR TM technology has already been used to detect copy number variation (Boettger et al 2012), viral load (Strain et al 2013), low-frequency transcripts , rare mutations or cell free DNA (Olmedillas-López et al 2017;Camunas-Soler et al 2018) among other applications.…”
Section: Introductionmentioning
confidence: 99%